Endogenous RNase inhibitor contributes to stability of RNA in crude cell lysates: Applicability to RT-qPCR - Wang, Xiao; Teferedegne, Belete; Shatzkes, Kenneth; Tu, Wei; Murata, Haruhiko (Analytical biochemistry, 2016)
Crude cell lysates are increasingly used as input for direct analysis by reverse transcription quantitative PCR (RT-qPCR), particularly for high-throughput applications. We previously demonstrated that a simple buffer containing a non-ionic detergent can serve as an inexpensive alternative to commercial cell-lysis reagents for the preparation of RT-qPCR-ready cell lysates; addition of an exogenous RNase inhibitor (RI) to the lysis buffer was found to be unnecessary to maintain RNA stability in cell lysates either freshly prepared or previously stored frozen at −80 °C. In the present study, we have demonstrated that the stability of RNA observed in our cell lysates is due to the presence of the endogenous RI. Furthermore, we have established the generalizability and applicability of this phenomenon by evaluating lysates prepared from cell lines commonly used in virology (A549, HeLa, MDCK, and Vero). Awareness of the mechanism underlying RNA stability may engender greater confidence in generating cell lysates for RT-qPCR without relying on addition of exogenous RI (a substantial cost-saving benefit) and encourage appropriate practices for handling and storage of samples.